PERPINDAHAN ONTOGENETIK HABITAT IKAN DI PERAIRAN EKOSISTEM HUTAN MANGROVE - Findra, Muhammad Nur; Hasrun, La Ode; Adharani, Nadya; Herdiana, Lella (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Ontogenetic of fish is a term used to study the development of the behavior of an individual throughout its life (life-span) from hatched to death. The mangrove ecosystem is a potential habitat for fish, especially the juvenile stage. Juvenile found in this habitat is an important economically fish. In various types of fish, the phenomenon of increasing the size of the fish body followed by changes in the types of food causing ontogenetic habitat of fish. It is evident in yellow snapper Lutjanus argentiventris. The juveniles live in mangrove habitat to approximately 100 mm or 300 days old, after which the fish move to deeper surrounding habitat. Mangrove forest that has a high complexity is to serve as an adaptation of fish to avoid predators and foraging. Several different habitats, both the mangrove ecosystem and other ecosystems provide different foods according to the needs at each phase-change of fish life. Animals that undergo ontogenetic habitat drift has management consequences that are more sensitive than animals inhabiting on single habitat. Hence, particularly habitat conservation resource management is needed. Not only conservation of the habitat, but also other habitats related to the migration of fish. Keyword: conservation, diet, growth, mangrove, ontogenetic